Lucid dreaming project - Gackenbach, Jayne (My University, 1980)
Although lucid dreams, awareness of dreaming while in the dream state, are not mentioned directly in the Edgar Cayce readings, the conceptually similar phenomena of astral projection or out-of-body experiences (OOBE) are touched upon. (Sparrow, 1976) The exact relationship between OOBEs and dream lucidity is unknown. Some feel that they represent different perceptions of the same experience (Sparrow, 1976; Schapiro, 1975-76), while others view them as conceptually distinct phenomena with some similarities. (Green, 1968; Donahoe, 1974)
Keywords: dreams; unconciousness